Dysregulation of lysine acetylation in the pathogenesis of digestive tract cancers and its clinical applications - Li, Penghui; Xue, Yuan (Frontiers in Cell and Developmental Biology, 2024)
Recent advances in high-resolution mass spectrometry-based proteomics have improved our understanding of lysine acetylation in proteins, including histones and non-histone proteins. Lysine acetylation, a reversible post-translational modification, is catalyzed by lysine acetyltransferases (KATs) and lysine deacetylases (KDACs).Proteins comprising evolutionarily conserved bromodomains (BRDs) recognize these acetylated lysine residues and consequently activate transcription. Lysine acetylation regulates almost all cellular processes, including transcription, cell cycle progression, and metabolic functions. Studies have reported the aberrant expression, translocation, and mutation of genes encoding lysine acetylation regulators in various cancers, including digestive tract cancers. These dysregulated lysine acetylation regulators contribute to the pathogenesis of digestive system cancers by modulating the expression and activity of cancer-related genes or pathways. Several inhibitors targeting KATs, KDACs, and BRDs are currently in preclinical trials and have demonstrated anti-cancer effects. Digestive tract cancers, including encompass esophageal, gastric, colorectal, liver, and pancreatic cancers, represent a group of heterogeneous malignancies.However, these cancers are typically diagnosed at an advanced stage owing to the lack of early symptoms and are consequently associated with poor 5-year survival rates.Thus, there is an urgent need to identify novel biomarkers for early detection, as well as to accurately predict the clinical outcomes and identify effective therapeutic targets for these malignancies. Although the role of lysine acetylation in digestive tract cancers remains unclear, further analysis could improve our understanding of its role in the pathogenesis of digestive tract cancers. This review aims to summarize the implications and pathogenic mechanisms of lysine acetylation dysregulation in digestive tract cancers, as well as its potential clinical applications.